LEGAL CHALLENGES OF ADOPTING AGE-VERIFICATION TECHNIQUES FOR THE PROTECTION OF MINORS ON THE INTERNET IN MALAYSIA - Manique Cooray (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The Internet has become the current form of distribution and communication of information in almost all segments of society. As children are leading increasingly connected lives, the Internet has become the primary source of information and a vital part of their social lives. The danger of such reliance by children on the Internet is that they could be victims of the misuse of the medium. Although the National Policy objectives of the communications and multimedia industry in Malaysia as stated in the Communications and Multimedia Act 1998 (CMA â€™98) is to regulate for the long-term benefit of the end-user, various reported cases, demonstrate that many children are exposed to pornographic and obscene material online. Such exposure amounts to â€œonline child abuse.â€ Research has indicated a paedophile makes use of such content to desensitize a child into believing that sexual acts depicted in pornographic movies are â€œnormalâ€ and hence it is acceptable for a child to engage in such behaviour thereby leading to the making of online child pornography and online grooming in the form of teaching the child to communicate in obscene language among others. Although the Penal Code and the CMA â€™98 make it an offence to distribute and make available such content in Malaysia, pornographic material can easily be accessed from websites originating from external servers. The objective of this paper is to propose a model for preventing the potential harms that might befall a child from accessing pornographic content online by ensuring that service providers adopt an â€œage-verificationâ€ control mechanism when such content is accessed in Malaysia. This is achieved through a reputable personal digital identity management service system to determine proof of age by children. However, in order for such a system to be put in place, the paper examines the legal challenges in the implementation of age-verification techniques for the protection of minors on the Internet in Malaysia.